7호 처분 집행의 법적 근거 명확화에 관한 연구 - 박찬걸; Park Chan-keol (소년보호연구, 2014)
According to the subparagraph 7, paragraph 1, article 32 of the current Juvenile Act, the judge of Juvenile Court can rule a disposition of 'entrusting to juvenile medical care facilities according to the law on treatment of hospital, sanitarium or protected juvenile' among the types of protective dispositions based on the hearing result. In this context, an issue is raised on whether ‘juvenile medical care facilities’ being referred to in subparagraph 7 disposition among the protective disposition of the Juvenile Act can be identified with medical & rehabilitation education juvenile hall' being referred to in the protective disposition ordinances. If it can be identified, an issue is raised on whether the disposition of subparagraph 7 also conform to 'the disposition of sending to juvenile hall'. It is because it could cause the result of subparagraph 7 also conforming to the disposition of sending to juvenile hall if juvenile medical care facilities are medical & rehabilitation education juvenile hall since in the existing discussion, the disposition of sending to juvenile hall commonly refers only to subparagraph 8 or 10 disposition among protective dispositions. In terms of the opposite case, if 'juvenile medical care facilities' being referred to in subparagraph 7 among protective dispositions in the Juvenile Act cannot be identified with 'medical & rehabilitation education juvenile hall' being referred to in protective disposition ordinances, it can be said that there is a gap in legislation only with existing ordinances due to lack of grounds to enforce subparagraph 7 at medical juvenile hall among the protective dispositions of paragraph 1, article 32 of the Juvenile Act. For such reason, it would be necessary to newly establish regulations related to the concept of 'juvenile medical care facilities' specified in the Juvenile Act, grounds in ordinances and grounds & principles of medical treatment. Hereinafter, the significance and contents of subparagraph 7 will be reviewed focusing on the necessity of subparagraph 7 disposition and process of change of organization in charge, period of subparagraph 7 disposition and status of recent dispositions, the cost burden issue of 'entrusted disposition such as hospital', status of transferring the subjects of subparagraph 9 & 10 dispositions to the subparagraph 7 disposition organization. In addition, it will examine existing discussions on re-establishment of the practical meaning of the entrusted disposition to juvenile medical care facilities and the concept of protected juvenile, as well as examine the status of legislative improvement. It will conclude the discussion by analyzing future assignments to supplement the task of clarifying legal grounds to enforce subparagraph 7 disposition.